Fragmentation of negative ions from N‐linked carbohydrates: Part 6. Glycans containing one N‐acetylglucosamine in the core. (30th September 2014) - Harvey, David J.; Edgeworth, Matthew; Krishna, Benjamin A.; Bonomelli, Camille; Allman, Sarah A.; Crispin, Max; Scrivens, James H.
<x xml:space="preserve">Abstract</x> RATIONALE Negative ion collision‐induced dissociation (CID) spectra of N‐glycans contain many diagnostic ions that provide more structural information than positive ion spectra. EndoH or endoS release of glycans from glycoproteins, as used by many investigators, cleaves glycans between the GlcNAc residues of the chitobiose core leaving the glycan without the reducing‐terminal GlcNAc residue. However, their negative ion CID spectra do not appear to have been studied in detail. This paper examines the CID and ion mobility properties of these endoH‐released glycans to determine if the missing GlcNAc influences the production of diagnostic fragment ions. METHODS N‐Glycans were released from ribonuclease B, ovalbumin and gp120 with endoH to give high‐mannose and hybrid glycans, and from IgG with endoS to produce biantennary complex glycans, all missing the reducing‐terminal GlcNAc residue. Negative ion CID and travelling wave ion mobility spectra were recorded with a Waters Synapt G2 mass spectrometer using nanospray sample introduction. RESULTS The majority of glycans yielded CID spectra exhibiting the same diagnostic fragments, which were equivalently informative, as the fully released structures. However, the ability of ion mobility to separate isomers was generally found to be inferior to its use with the full glycans despite the smaller nature of the compounds. The exception was the partial resolution of a pair of biantennary monogalactosylated glycans from IgG where, as chloride adducts, slight separation of the isomers was observed. CONCLUSIONS The results show that the CID spectra of endoH‐ and endoS‐released glycans are as useful as the corresponding spectra of the intact glycans (as released by PNGase F) in providing structural information on N‐glycans. Copyright © 2014 John Wiley & Sons, Ltd.